Confident data skills : master the fundamentals of working with data and supercharge your career - Eremenko, Kirill (Kogan Page, 2018)
"Learning how to work with data may seem intimidating or difficult but with Confident Data Skills you will be able to master the fundamentals and supercharge your professional abilities. Confident Data Skills covers data visualization, data modelling, data preparation, data communication and programming skills. In-depth international case studies from a wide range of organizations allow you to see successful data techniques in practice and provide a real-world basis to the knowledge you gain as you move through the book. To stretch and deepen your knowledge, the final part of the book explores more advanced data techniques to allow you to take your skills further. Guidance on how you can use data skills to enhance your employability is also given, providing invaluable business insight into how your new knowledge can help you take your career to new heights."--